GRAPHOANALYTIC DETERMINATION OF PARAMETERS RELAXATION DEFORMATION OF ROCKS BY DATA OF DEVELOPMENT OF DEPOSITS - Kazymov, B. Z (university of el oued/جامعة الوادي, 2019)
As a rule, to determine the deformation parameters of rocks, the results of the interpretation of the actual data of hydro-gas-dynamic studies of wells are used in the non-static mode. In the article, a technique different from this approach for determining the parameters of the relaxation deformation of rocks according to the data of the development of gas deposits is given. The proposed technique is characterized by its versatility due to the fact that, in contrast to the methods based on specially conducted hydro-gas-dynamic studies of wells, the field development data is used, and also changes in the real properties of the reservoir system, as saturation and super-compressibility factors of the gas
Articel
Keywords: Relaxation deformation, Relaxation time, Compressibility coefficient, Reservoir pressure